Securing the Food Supply Chain Amid Geopolitical Uncertainty: A Comprehensive Review - Rahayu, Lestari; Astuti, Retno; Soboh, Rafat (Department of Agro-industrial Technology, University of Brawijaya, 2024)
AbstractThe global food supply chain is highly vulnerable to geopolitical influences, affecting production and consumption activities. Recent geopolitical disruptions have highlighted the need for strategic foresight and risk management to enhance resilience. This study aims to analyze the multifaceted impact of geopolitical events on the food supply chain and propose strategies for enhancing its resilience and sustainability. A qualitative literature review was conducted, synthesizing findings from 50 peer-reviewed articles. Key findings reveal that geopolitical events such as conflicts, trade disputes, and regulatory changes significantly disrupt food supply chains, leading to food shortages and price volatility. Technological innovations and strategic foresight are critical in mitigating these impacts. Effective risk management, technological advancements, and adaptive governance frameworks are essential for building resilient food supply chains. Policymakers and stakeholders must collaborate to develop robust strategies that ensure food security in an increasingly volatile geopolitical landscape.Keywords: Food supply chain, geopolitical disruption, policy, resilience, risk management AbstrakRantai pasok pangan global sangat rentan terhadap pengaruh geopolitik yang memengaruhi aktivitas mulai dari produksi hingga konsumsi. Gangguan geopolitik baru-baru ini menyoroti bahwa tinjauan ke masa depan yang strategis dan manajemen risiko diperlukan untuk meningkatkan ketahanan ketahanan dan keberlanjutan rantai pasok pangan. Tinjauan literatur kualitatif dilakukan dengan mensintesis temuan dari 50 artikel jurnal. Temuan utama mengungkapkan bahwa peristiwa geopolitik seperti konflik, perselisihan perdagangan, dan perubahan peraturan secara signifikan mengganggu rantai pasok pangan sehingga menyebabkan kekurangan pangan dan ketidakstabilan harga. Inovasi teknologi dan tinjauan ke masa depan sangat penting dalam memitigasi dampak-dampak ini. Manajemen risiko yang efektif, kemajuan teknologi, dan kerangka tata kelola yang adaptif sangat penting untuk membangun rantai pasok pangan yang tangguh memastikan keamanan pangan dalam situasi geopolitik yang semakin bergejolak.Kata Kunci: Gangguan geopolitik, kebijakan, ketahanan, manajemen risiko, rantai pasok pangan